Mitigation of sand liquefaction under static loading condition using biogas bubbles generated by denitrifying bacteria. (1st October 2021) - Peng, Erxing; Sheng, Yu; Hu, Xiaoying; Zhang, Dingwen; Hou, Zheng
Abstract: Nitrogen bubbles that is generated by microbial denitrification process is a new pollution-free clean material for mitigation of sand liquefaction. The current study aims to assess sustainability as well as distribution character of biogas bubbles in sand column under the condition of hydrostatics along with its performance of mitigating sand liquefaction under static loading. A series of laboratory experiments were conducted, and test results indicate that biogas bubbles has excellent sustainability in sand pores, and after 92 weeks, an increase of saturation from 84.5 to 85.1% marking only 0.6% rise. The volume of biogas generated by bacteria increases linearly with decrease of depth. Under undrained condition, if saturation of sample decreased from 100% to around 92.4%, strain softening behavior will transfer to strain hardening, and undrained shear strength can be increased by approximately two times in both of compression and extension tests. The excess pore water pressure ratio and liquefaction potential index have significant reduction with the decrease of saturation, and the magnitude of impact on compression is comparatively bigger than the extension tests. This study validates that as a new material, biogas bubbles are very stable in soil, desaturation using nitrogen bubbles is an effective method for mitigating the liquefaction of sand under static loading conditions. Moreover, the study provides support for the desaturation mitigating static liquefaction of sand to prevent geological disasters and reveals its potential engineering practical value. Highlights: Desaturation using biogas bubble can effectively increase the liquefaction resistance under monotonic loading. Biogas bubbles show the long-term sustainability in pore of sand column under hydrostatic condition. Inducing biogas bubbles in sand pore can increase the initial peak value of sand strength.